Trajectories of Transcutaneous Oxygen (TcPO2) and Healing in Chronic Limb-Threatening Ischemia: A 12-Month Longitudinal Study - Kawamura Haruka; Asmat Burhan; Inoue Nanami; Fujita Kento (Indonesian Science Media, 2025)
Background: Chronic limb-threatening ischemia (CLTI) remains a major global burden with high amputation risk, while evidence on using transcutaneous oxygen pressure (TcPO₂) trajectories (level + slope) to guide healing decisions is limited. Most studies treat TcPO₂ as a static threshold, not a time-updated signal that could trigger earlier escalation. Purpose: This study aimed to estimate the association of TcPO₂ trajectories and revascularization with wound-healing probability among patients with CLTI over 12 months. Methods: In a prospective longitudinal cohort at a Japanese hospital (Mar 3, 2023- Mar 1, 2024), we enrolled 46 adults with tissue-loss CLTI meeting guideline ischemia criteria; acute limb ischemia and non-ischemic ulcers were excluded. Standardized wound care was provided; revascularization was time-varying (from procedure date). TcPO₂ was measured at baseline, 2, 4, 8, 12 weeks, and 6, 9, 12 months. The primary outcome was complete epithelialization sustained for ≥2 visits. Discrete-time survival models estimated adjusted odds ratios (aORs) with 95% CIs, adjusting for age, diabetes, infection, albumin, WIfI ischemia grade, and smoking; sensitivity analyses included competing risks and joint modeling. Results: Among 46 participants (mean age 71 years; diabetes 78%; CKD 41%), baseline mean TcPO₂ was 18.3 mmHg (standard care 21.2; revascularization 16.3). From baseline to Week 12, TcPO₂ rose +2.9 mmHg under standard care versus +15.8 mmHg post-revascularization. Higher time-updated TcPO₂ and positive slope independently increased healing (per 10 mmHg aOR 1.62, 95% CI 1.24-2.11; per 1 mmHg/week aOR 1.48, 1.12–1.97). Revascularization was beneficial (aOR 2.35, 1.18-4.68), while visit-level infection reduced healing (aOR 0.58, 0.36-0.92). Effects were directionally robust across sensitivity analyses. Conclusion: Trajectory-based TcPO₂ monitoring (level and slope) identifies an early, actionable window after baseline especially post-revascularization when timely escalation can improve healing. Findings support embedding serial TcPO₂ into CLTI care and motivate multicentre evaluations of effectiveness, cost, and equity.